The Effect of Learning Strategy and Writing Motivation on the Ability to Write Short Texts during Covid-19 Pandemic - Arif Yuandana Sinaga; Nova Erawati Sidabolak (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to compare how students taught with Learning Strategies for Improving Thinking Skills (SPPKB), and expository learning strategies to write short stories. Additionally, it identifies differences in students' short story writing abilities between those with a high level of writing motivation and those with a low level of writing motivation. Additionally, it establishes the relationship between learning strategies and motivation for writing short stories in online learning. Diponegoro High School is located in the Asahan Regency. This research was conducted at Diponegoro Senior High School in Asahan Regency, with tenth-grade students as the research population. This is a quantitative study conducted using quasi-experimental methods. A Randomized Control Group Pretest-Posttest Design was used in the research. Instruments include treatment instruments such as syllabuses, lesson plans, questionnaires, and measurement instruments embedded in short story texts. The study's findings indicate a difference in the ability to write short stories between the treatment of learning strategies and motivation to write, and that this difference is mediated by an interaction.